Modelling the influence of the process inputs on the removal of surface contaminants from Ti-6Al-4V linear friction welds - McAndrew, Anthony; Colegrove, Paul A.; Addison, Adrian C.; Flipo, Bertrand C. D.; Russell, Michael J. (Elsevier, 2014)
The linear friction welding (LFW) process is finding increasing interest from industry for the fabrication of near-net-shape, titanium alloy Ti–6Al–4V, aerospace components. Currently, the removal of surface contaminants, such as oxides and foreign particles, from the weld interface into the flash is not fully understood. To address this problem, two-dimensional (2D) computational models were developed using the finite element analysis (FEA) software DEFORM and validated with experiments. The key findings showed that the welds made with higher applied forces required less burn-off to completely remove the surface contaminants from the interface into the flash; the interface temperature increased as the applied force was decreased or the rubbing velocity increased; and the boundary temperature between the rapid flash formation and negligible material flow was approximately 970 °C. An understanding of these phenomena is of particular interest for the industrialisation of near-net-shape titanium alloy aerospace components.
Keywords: Linear friction welding; Additive manufacture; Modelling